Changes caused by the use of chlohexidine mouthwash in composite bulk-fill (in vitro). (29th March 2019) - Furtado, M. M.; Amorim, A.
Abstract : Introduction: The aesthetic requirements of dental restorations, and the technological evolution of composite resins allowed their use in posterior teeth at the expense of the traditional amalgam [1 ]. The discoloration, wear resistance and susceptibility of plaque retention are factors to be taken into account [2 ] Chlorhexidine (CHX), frequently used in dental medicine in the treatment of oral candidiasis, gingivitis and periodontitis, among others is a cationic antiseptic with high potential for pigmentation of teeth and soft tissues [3 ] There are several studies that demonstrate the effects of chlorhexidine and its mechanisms on discoloration and surface changes of nano and micro hybrid composites. Yet there is few research regarding the effects on composite bulk-fill, for posterior teeth, different in terms of resistance to stress, contraction and depth of polymerization, The aim of this study is to evaluate the colour change and surface degradation of four different colour bulk- fill resins, after immersion in three different chlorhexidine (CHX) based mouthwashes. Materials and methods: 136 cylindrical samples, 4 mm in ø by 4 mm in depth, A1, A2, A3 and C2 of Filtek ™ One bulk- fill restorative composites. The samples were subjected to a daily immersion with Vortex agitation for 15 consecutive days in different solutions: distilled water (control) and chlorhexidine (CHX) mouthwashes (0.05%, 0.1% and 0.12%). Among the immersions, the samples were stored in distilled water at 37° C. The colour of the samples was evaluated with a spectrophotometer before and after the immersions [4 ]. The colour changes were calculated using the CIE system L * a * b *. At the end of the laboratory procedures, 3 random specimens from each group were selected to analyse the surface roughness with the Scanning Electron Microscope (SEM). The results obtained by the spectrophotometer analysis were statistically treated by the SPSS software, using descriptive and comparative statistics (bidirectional ANOVA and 95% CI), with a significance level of 5%. Results: Bulk-fill composites showed clinically unacceptable colorimetric alterations in samples submitted to the 0.1% CHX mouthwash immersion, as well as C2 colour specimens treated with a mouth rinse with 0.12% of CHX. The greatest surface degradation was that on the samples treated with 0.1% CHX rinse. Discussion and conclusions: The alcohol (ethanol), being a bipolar molecule, triggers a dissolution of the hydrophobic and hydrophilic components of the resins [5 ]. Studies show that dimethacrylates are more susceptible to the effect of alcohol. The composites used contained 3 dimethacrylates, AUDMA, DDDMA and UDMA. This fact may justify the colorimetric alteration and the great change in the surface morphology caused by the mouthwash at 0.1% CHX (with the highest alcohol content) [6 ]. In this sense, it was possible to verify that for all the resins under study, the mouthwash with 0.1% CHX (Eludril CLASSIC) was the one that triggered colorimetric changes clinically unacceptable (ΔE> 3.3) and visible. Bulk-fill composites were submitted to morphology and colour changes when exposed to the action of different mouthwashes based on CHX. The intensity of changes on the surface morphology varied according to the CHX concentration of the mouthwashes and alcohol content. Results are very similar to those obtained for other types of composites